Occlusal Trauma Restored with a Fiber-Reinforced Composite Resin System (FRC) - Ramírez Barrantes, Juan Carlos (2021)
Fiber-reinforced composite resin systems (FRC) are widely used materials in engineering and biomedicine. For approximately 40 years they have been investigated demonstrating their excellent mechanical properties. From a clinical perspective, they are suggested in different disciplines of dentistry, where their applications are evidenced-based. With the introduction of new technologies and bonding protocols, these types of materials can be used as substructures. The attempt to explore the properties and applications of FRC's materials in non-everyday clinical cases, allows us to provide a viable alternative in the planning of complex restorative treatments.